Full Range of Motion Induces Greater Muscle Damage Than Partial Range of Motion in Elbow Flexion Exercise With Free Weights. Issue 8 (August 2017) - Baroni, Bruno M.; Pompermayer, Marcelo G.; Cini, Anelize; Peruzzolo, Amanda S.; Radaelli, Régis; Brusco, Clarissa M.; Pinto, Ronei S.
Abstract : Abstract: Baroni, BM, Pompermayer, MG, Cini, A, Peruzzolo, AS, Radaelli, R, Brusco, CM, and Pinto, RS. Full range of motion induces greater muscle damage than partial range of motion in elbow flexion exercise with free weights. J Strength Cond Res 31(8): 2223–2230, 2017—Load and range of motion (ROM) applied in resistance training (RT) affect the muscle damage magnitude and the recovery time-course. Because exercises performed with partial ROM allow a higher load compared with those with full ROM, this study investigated the acute effect of a traditional RT exercise using full ROM or partial ROM on muscle damage markers. Fourteen healthy men performed 4 sets of 10 concentric-eccentric repetitions of unilateral elbow flexion on the Scott bench. Arms were randomly assigned to partial-ROM (50–100°) and full-ROM (0–130°) conditions, and load was determined as 80% of 1 repetition maximum (1RM) in the full- and partial-ROM tests. Muscle damage markers were assessed preexercise, immediately, and 24, 48, and 72 hours after exercise. Primary outcomes were peak torque, muscle soreness during palpation and elbow extension, arm circumference, and joint ROM. The load lifted in the partial-ROM condition (1RM = 19.1 ± 3.0 kg) was 40 ± 18% higher compared with the full-ROM condition (1RM = 13.7 ± 2.2 kg). Seventy-two hours after exercise, the full-ROM condition led to significant higher soreness sensation during elbow extension (1.3–4.1 cm vs. 1.0–1.9 cm) and smaller ROM values (97.5–106.1° vs. 103.6–115.7°). Peak torque, soreness from palpation, and arm circumference were statistically similar between conditions, although mean values in all time points of these outcomes have suggested more expressive muscle damage for the full-ROM condition. In conclusion, elbow flexion exercise with full ROM seems to induce greater muscle damage than partial-ROM exercises, even though higher absolute load was achieved with partial ROM.